Is a Fixed Hybrid Prosthesis with Distal Cantilever Appropriate for Maxillofacial Defects? A Report of Two Patients. Issue 1 (6th June 2016) - Altintas, Subutay Han; Kilic, Serdar; Yilmaz Altintas, Nuray; Cizmeci Senel, Figen
Abstract: The most important objectives in restoring the maxillofacial patient are the restoration of function and psychological improvement through esthetics. Acquired maxillary and mandibular defects due to significant trauma or surgery represent a major challenge for the clinician and patient. Dental implant‐retained prostheses represent a well‐documented and reliable treatment option and can also help patients with maxillofacial defects by eliminating denture instability and improving function. Full‐arch fixed dental hybrid prostheses provide functional and psychological advantages and also reduce the load on vulnerable soft and hard tissues in the reconstruction area. Two clinical reports are presented describing the prosthetic rehabilitation using dental implant‐supported fixed hybrid prostheses with clinical and radiographic follow‐up of 3 years.